Trust, buybacks and equity issues - HUANG, Sterling (Institutional Knowledge at Singapore Management University, 2018)
In this paper, we find that public trust has a significant positive impact on short- and long-term excess returns after buyback announcements and equity issues. In addition to proxies for the likelihood of undervaluation (for buybacks) and overvaluation (for equity issues), the trust variable is the most robust predictor. We also find that stated motivations for buybacks such as “undervaluation” are more credible in counties with high trust levels.